Peciuliar Passive Expressions of Japanese - Devėnaitė, Violeta (Acta Orientalia Vilnensia, 2004)
The article deals with Japanese passive expressions and features of the usage of Japanese passive voice, introduces interpretations of the meaning of Japanese passive expression and the classification of the passive sentences. The explanation of the case necessary for the agent and the subject (receiver of the action) and the importance of unification of the viewpoint is also presented.The main conclusions are as follows:The scope of the usage of the passive voice in Japanese is wider than in Lithuanian, and there are a lot of Japanese passive sentences to which an interpretation of the Lithuanian passive “The agent did something, and the receiver of action entered such a state” does not apply.It can be said that some Japanese passive sentences, e.g., indirect passive sentences, are not so easy to understand even for intermediate and advanced level Japanese learners.The concept of the agent is not identical in Lithuanian and Japanese.The understanding of the concept of the agent is not identical even among Lithuanian learners of Japanese. There are a lot of learners who make a passive sentence relying on mother tongue and those who cannot unite the viewpoint of a sentence.The japanese passive voice means receiving influence of action (good or bad for speaker) regardless of the intention of the speaker (out of the range which the speaker can control). It means that “the receiver of action cannot know what happens and, moreover, cannot stop it.”